Study on the co-combustion mechanism of coal gangue and coal gasification fly ash based on thermogravimetric mass spectrometry - Jiangong LIN; Xiaoyu ZHANG; Jicheng HUI; Shujun ZHU; Jianguo ZHU (Meitan xuebao)
The combustion characteristics and gas release characteristics of the Wuhai coal gangue, the Suqian coal gasification fly ash, and their mixtures were revealed by thermogravimetric mass spectrometry analysis. The co-combustion mechanism of the Wuhai coal gangue and the Suqian coal gasification fly ash was studied by combining the physicochemical properties of the two fuels. The thermogravimetric analysis results indicate that the Wuhai coal gangue has better ignition characteristics than Suqian coal gasification fly ash. The ignition characteristics of the mixtures are improved by the Wuhai coal gangue, while the high-temperature combustion characteristics are improved by the Suqian coal gasification fly ash. The combustion kinetics were analyzed based on the Coats-Redfern (C-R), Flynn-Wall-Ozawa (FWO), and Kissinger-Akahira-Sunose (KAS) methods. The results show that the apparent activation energy of the Wuhai coal gangue is 48.25−152.22 kJ/mol, and the combustion reaction conforms to the Jander model. The apparent activation energy of the Suqian coal gasification fly ash is 106.34−312.79 kJ/mol, and the reaction conforms to the reaction level model with n=1/4. When the mass ratio of the Wuhai coal gangue to the Suqian coal gasification fly ash was 1∶3, the apparent activation energy was 102.24−301.58 kJ/mol, which corresponds to the synthesis of a nuclear growth model. The interaction of these fuels was examined by comparing the deviation between the theoretical and experimental weight loss rate of mixtures. The results show that there is a significant coupling effect between the Wuhai coal gangue and the Suqian coal gasification fly ash, mutually enhancing their combustion characteristics. This promoting effect is gradually strengthened with the increasing mass proportion of the Suqian coal gasification fly ash. Based on the comprehensive co-combustion characteristics and gas release characteristics, the better mass ratio of the Wuhai coal gangue to the Suqian coal gasification fly ash is 1∶3. NH3 is released during the volatile fraction and fixed carbon combustion process. The temperature corresponding to the peak intensity of the NO and NO2 release is essentially consistent with the temperature corresponding to the maximum reaction rate on the thermogravimetric curve.